Structural and Interfacial Properties of Hyperbranched-Linear Polymer Surfactant - Qiang, Taotao (Springer Berlin Heidelberg, 2014)
With oleic acid grafting modification, a series of hyperbranched-linear polymer surfactants (HLPS) were prepared by hydroxyl-terminated hyperbranched polymer (HBP), which was gained through a step synthesis method using trimethylolpropane and AB(2) monomer. The AB(2) monomers were obtained through the Michael addition reaction of methyl acrylate and diethanol amine. The structures of HLPS were characterised by Fourier transform infrared spectrophotometer and nuclear magnetic resonance (NMR), which indicated that HBP was successfully modified by oleic acid. Furthermore, the properties of surface tension and critical micelle concentration of HLPS solution showed that HLPS can significantly reduce the surface tension of water. The morphology of the HLPS solution was characterised by dynamic light scattering, which revealed that HLPS exhibited a nonmonotonic appearance in particle size at different scattering angles owing to the different replaced linear portions. The relationships of the surface pressure to monolayer area and time were measured using the Langmuir–Blodgett instrument, which showed that the surface tension of monolayer molecules increased with the increasing of hydrophobic groups. In addition, the interface conditions of different replaced HLPS solutions were simulated. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s11743-014-1592-3) contains supplementary material, which is available to authorized users.